A scoping review of racism and anti-racist solutions in the health care of people who have experienced trafficking. - Brooke Bernardin; Sakshi Garg; Fajr Khan; Yewon Lee; Carrie Wade; Hanni Stoklosa (PLoS ONE)
Racial minorities are disproportionately affected by human trafficking, with African Americans making up over 30% of trafficking cases in the United States despite being only 14% of the national population. Health care providers play a crucial role in identifying and supporting survivors of trafficking as roughly two-thirds of individuals who have been trafficked encounter a healthcare professional. However, discrimination against trafficked patients of color in health care, a key setting for frontline service provision, remains unexplored. We undertook a scoping review to identify the effects of racial and ethnic discrimination in the healthcare of individuals who have experienced human trafficking, with the aim of informing anti-racist practice, treatments, interventions, and research. Following the PRISMA extension for scoping reviews (PRISMA-ScR), we identified 41 sources comprising quantitative and qualitative studies, case reports, grey literature, and text and opinion pieces. Quantitative studies indicated that there are significant gaps in service availability for Black, Indigenous, and People of Color (BIPOC) survivors in the midwestern United States. Our remaining sources suggested that healthcare provider bias and discrimination emerged through victim blaming, adultification, criminalization, or invisibility of BIPOC survivors. Racism was also perpetuated structurally through lack of culturally relevant training, fear of punishment from police or immigration enforcement, and sociocultural barriers to accessing healthcare. Furthermore, we identified best practices for future anti-trafficking efforts in health care on several levels including treatment, research, intervention design and evaluation, community partnerships, coalition-building, and political advocacy. Ultimately, healthcare providers have a unique opportunity to respond to human trafficking, but to do so effectively will require comprehensively addressing critical gaps in care for BIPOC populations across individual, interpersonal, and structural levels.